Mifepristone-misoprostol combination in medical termination of early pregnancy - Pitale, Devdatt Laxman (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Unplanned and unwanted pregnancies are common worldwide despite of the medical advancements and wider availability of contraceptive methods. The development of safe, effective, inexpensive, nonsurgical methods of abortion is thus highly desirable. Objective of present study was to evaluate the effectiveness of Mifepristone 200 mg orally followed by Misoprostol 800 µg intravaginally 48 hours later in women undergoing medical termination of early pregnancy (up to 63 days of gestational age). Methods: The present study included 100 pregnant women requesting termination of pregnancy in first trimester attending the department of Obstetrics and Gynecology. Women with gestational age up to 63 days from the first day of the last menstrual period with previous regular cycles were studied. Patients without medical or surgical contraindications to Mifepristone and Misoprostol were included. Results: Majority of the pregnant women belonged to the age group between 20-30 years. 30% of these women were nulliparous and 70 % were multiparous. The period of gestation varied from 35-63 days.90% of the patients had complete abortion and 10% had incomplete abortion. All the patients expelled the products of conception within 24 hours of prostaglandin administration. The adverse effects reported were nausea reported by 30%, vomiting by 5 %and diarrhea by 2% of the cases. None of the patients reported excess bleeding at the time of abortion, hospitalization or blood transfusion. This regimen has the effectiveness of complete abortion rate with few side effects. Conclusions: The Mifepristone- Misoprostol combination offers an effective, acceptable, out-patient procedure and an alternative to surgical methods of abortion in medical termination of early pregnancy (up to 63 days of gestation).